Implementation of Voltage Optimization for Sustainable Energy - Jian Ding Tan; Siaw Paw Koh; Mau Teng Au; Sieh Kiong Tiong; Kharudin Ali (Institute of Advanced Engineering and Science, 2018)
The voltage control in the power distribution network is challenged firstly by constantly increasing in power demand and secondly by a growing number of distributed connections, which significantly changes the load flow in the network. Situation is worsening with the current heavily implemented micro-generation of Solar PV. Consequently, the uncontrollable rapid changes in the power distribution network would affect voltage instability at the feeder with wide area power demand. Voltage instability would affect the energy efficiency of the electrical equipment. Moreover, the lifespan of some equipment would be shortened due to the excessive and unstable voltage supplied. The proposed research aims to implement the low impedance voltage optimization system in solving the existing problem. The voltage optimization system had been tested on both resistive and inductive loads. The power consumption of the loads had been measured at a few discrete values of voltage optimization within the statutory region. Further tests were conducted on industrial water pump, general lightings with mixed loads, office building, restaurant and plastic injection moulding machine. The power measurements were logged and the results in term of power consumption were analysed. The results showed that the proposed optimization mechanism successfully optimize and saved 6.81%, 14.42%, 13.97%, 12.23%, and 26.23% of the power consumptions in respective tests.